John Greenleaf Whittier: A sketch of his life, with selected poems - Perry, Bliss, 1860-1954; Whittier, John Greenleaf, 1807-1892 (Salt Lake City, UT : Project Gutenberg, 2022)
"John Greenleaf Whittier: A Sketch of His Life, with Selected Poems" by Bliss Perry et al. is a biographical account interspersed with poetry written in the early 20th century. This volume not only chronicles the life of John Greenleaf Whittier, an influential American poet and abolitionist, but also includes selected works to illustrate key themes from his life and literary contributions, particularly his engagement with social issues and personal reflections on his upbringing. The opening of this work outlines the solitary and formative environment of Whittier's early life in rural New England, emphasizing the intimacy he had with nature, his family's Quaker beliefs, and the simplicity of his upbringing. Perry highlights Whittier's intellectual and emotional isolation, paired with an early affinity for poetry sparked by the work of Robert Burns. As Whittier's youth unfolds, we see him endure hardships while developing a rich inner life, leading to his eventual commitment to both poetry and activism, especially in the abolitionist movement, which would define much of his later work. (This is an automatically generated summary.)
"The occasion for this little volume is the celebration of the centenary of Whittier's birth"--Note.
Release date is 2022-01-19
Richard Tonsing and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Poets, American -- 19th century -- Biography; American poetry -- 19th century; Whittier, John Greenleaf, 1807-1892